Tween–80 Coating in Enhancing Physicochemical Stability, Kinetics and Release Mechanism of Layered Double Hydroxide-Ferulate - Sharifah Norain Mohd Sharif; Norhayati Hashim; Illyas Md Isa; Maizatul Najwa Jajuli; Afif Arifin; Norlaili Abu Bakar; Mazidah Mamat; Suyanta Suyanta (Universitas Gadjah Mada, 2024)
This study aims to enhance the targeted delivery of a powerful antioxidant, ferulate (FA), by developing a controlled release formulation (CRF) based on the incorporation of layered double hydroxide and Tween-80 polymeric surfactant. The layered double hydroxide-ferulate (LDH-FA) synthesized by co-precipitation method was homogenously mixed with the Tween-80 coater under continuous stirring. The successful Tween-80 coating was verified with PXRD analysis and supported by FTIR. No changes in interlayer distance between LDH-FA (at 17.4 and 8.7 Å) and LDH-FA-T80 (at 17.6 and 8.6 Å) were observed in the PXRD pattern. TGA/DTG analysis demonstrated good thermal stability of LDH-FA-T80, with the ability to withstand extreme temperatures up to 460 °C. The association of Tween-80 with LDH-FA progressively sustained the release time of FA in each aqueous solution, with a release time of up to 440 min. For both LDH-FA and LDH-FA-T80, the release of FA is through dissolution and anion exchange release mechanism (regulated by pseudo-second-order kinetic model). The study's findings suggest practical applications of FA in the pharmaceutical industry by implying the retarding effect triggered by Tween-80, offering new insights for the application of CRF to enhance the therapeutic effect of FA.